Determination of adhesion between corrosion product film and carbon steel by a scratch test. Issue 10 (5th November 2012) - Zhu, X. L.; Lu, X. F.; Ling, X.
Abstract A scratch test is used to measure the adhesion between corrosion product film (CPF) and carbon steel in deionized water under different pH and temperatures. The fuzzy feature model is modified to minimize errors between calculation and scanning electron microscopy (SEM) results. Findings illustrate that the maximum error decreases to 11%. The adhesion between CPF and substrate increases with rising temperature and pH of deionized water. The Poisson's ratio and Young's modulus of CPF are in the ranges [0.34 and 0.45] and [0.08 and 0.11 GPa], respectively, as temperature and pH change.